Genetic association meets RNA interference: large-scale genomic screens for causation and mechanism of complex diseases. (May 2007) - Martin, Mitchell; Reidhaar-Olson, John F; Rondinone, Cristina M
While the genomic era offers great promise for biomedicine in general and for biomarker discovery in particular, it has yet to significantly impact drug target discovery. Meanwhile, despite improvements over the past 20  years in reducing attrition in clinical trials due to adverse drug responses, the pharmaceutical industry continues to be beset by the high rate of attrition of compounds in late-stage development, primarily due to the lack of drug efficacy. Clearly, even highly potent drugs with ideal safety and pharmacokinetic profiles will fail to survive clinical trials if the drug target itself is not a key point of intervention for most patients. Genetic association studies and RNA interference are two scaleable genomic approaches that together can address the quality as well as quantity of candidate drug targets. Human genetic information has long been used to identify ''molecular bottlenecks'' that can highlight the importance of a gene or pathway at the clinical level. The recent availability of the human HapMap and of high-throughput genotyping platforms now enables more systematic genetic screens for novel, clinically-relevant drug targets. In addition, RNA interference can help dissect the molecular role of a candidate drug target in preclinical model systems in  vitro and in  vivo . Wider applicability of RNA interference methods will closely follow continued progress on efficient delivery into appropriate cell models and target tissues.